PENDIDIKAN ISLAM MULTIKULTURAL DAN INTEGRASI BANGA - Sri HaryatI; Desy Eka Citra Dewi (STKIP Subang, 2025)
Islamic Education (PAI) research increasingly faces complex challenges related to students’ religious attitudes, learning motivation, and diverse socio-religious backgrounds. These issues indicate that PAI phenomena are multidimensional and cannot be adequately understood using a single research approach. This study aims to analyze how mixed methods can be integrated effectively within PAI research in terms of conceptual foundations, research designs, and methodological applications. Using a library research approach, this study collected, classified, and analyzed relevant literature from books, journal articles, and previous studies that implemented mixed methods in Islamic education. The findings show that mixed methods offer comprehensive and adaptive advantages by combining quantitative data, which reveal general patterns of religious understanding and learning outcomes, with qualitative data, which provide deeper insights into students’ spiritual experiences, motivations, and contextual factors affecting their religious behavior. Three dominant designs were identified as most relevant for PAI research: convergent parallel, explanatory sequential, and exploratory sequential. Each design contributes uniquely to strengthening the validity, depth, and interpretive power of research findings. Overall, mixed methods serve as a methodological necessity for studying complex phenomena in Islamic education, enabling holistic, credible, and contextually grounded conclusions.